Serões gramaticais: a gramática "científica" de Ernesto Carneiro Ribeiro - Rodrigues, Ana Lúcia (2009)
This dissertation is in the line of research related to History and Description of the Portuguese Language, of the program of post-graduation studies of Portuguese Language of Pontifícia Universidade Católica de São Paulo and it has as an object of study the work Serões gramaticais, of Ernesto Carneiro Ribeiro. The main objective of this research is to verify how much the author has adhered to the historical-comparative method when producing his grammar. The relevance of this work lies in the purpose of innovation on the part of the author, although he has not abandoned tradition totally. The investigation is supported by the theoretical assumptions of History of Linguistic Ideas, and the results thereof have shown that the historical, social, political, economic and educational moment has influenced Ernesto Carneiro Ribeiro in the production of his grammar